Relationship Between Dynamics of Plant Biometric Parameters and Leaf Area Index of Hop (Humulus lupulus L.) Plants - Václav Brant; Karel Krofta; Petr Zábranský; Pavel Hamouz; Pavel Procházka; Jiří Dreksler; Milan Kroulík; Gabriela Fritschová (Agronomy)
Biometric parameters of hop plants were studied over a three-year period on the Czech variety Premiant grown in the Žatec (Saaz) hop-growing region under an organic farming regime. Initially, only bine leaves developed, with lateral leaves emerging during the third growing month (June). Their leaf area at the time of harvest was larger than the bine leaves. The moment when the area size of both leaf categories was the same, designated as the breaking point (BP), was determined in the interval 181–195 DOY (day of year). The leaf area (LA) measured using infrared imaging and gravimetric methods yielded comparable results, with correlation coefficients of 0.93 and 0.96, respectively. The total leaf area of one hop plant (LA) with four trained bines, which developed dynamically during ontogeny, was 10.45 m2 (2019), 6.65 m2 (2020), and 12.04 m2 (2021) in the harvest period. With a spacing of 3 m × 1 m, the corresponding Leaf Area Index (LAI) values were 3.5, 2.2 and 4.0 in the harvest season. Therefore, they are comparable to other crops such as maize or sorghum. Regression equations were calculated to determine the dry biomass of bine and lateral leaves depending on DOY. Correlations between the dry mass of leaves and the size of the leaf area for both bine and lateral leaves were also evaluated. This work also contains data on the mass proportions of the main plant organs (bine, leaves, cones).